Implementation of Tempo in Rhythmic Music Learning in a Pandemic Period for Junior High School Students - Heidar, Faraz Hilmi; Maryanti, Rina; Wulandary, Verra; Irawan, Asep Rudi (LPPM Universitas Jenderal Achmad Yani, 2022)
The learning system in teaching and learning activities during this pandemic provides its own challenges for teachers in delivering learning materials so that they are conveyed well to students. The purpose of this research is to maximize and organize rhythmic music learning during the Covid-19 pandemic. To support this research, we conducted a quantitative descriptive research method. The research was conducted in Junior High School. With the method of giving pretest-posttest. The data collection technique used is through Google Form. The material provided is in the form of a video about rhythmic music, which students are then required to understand technically according to what has been taught in the video. This research was conducted before and after giving the material to determine the level of students' understanding of the material. From the data obtained from the Google Form results, it shows that as many as 31.5% of students can process the tempo well, and it can also be seen how far the level of students' understanding of the material that has been taught, we can find some of the students' abilities in processing tempo through rhythmic so that it can be practiced in the musical instrument.